2001
DOI: 10.1002/jbm.1058.abs
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent mechanical properties of HA/TCP particles in relation to morsellized bone grafts for use in impaction grafting

Abstract: Abstract:In reconstructive surgery human bone defects are sometimes filled with the use of the impaction bone grafting technique. Currently different types of biomaterial particles are being developed as bone-substitute materials. Before these biomaterials can be applied their mechanical and biological behavior should be characterized. In this study the timedependent mechanical behavior of biomaterial particles with different tri-calcium-phosphate/ hydroxy-apatite (TCP:HA) ratios, particle sizes, and porositie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…While some variations are expected due to inter-sample variations, such a large range has to be due to other factors. The reported values are seen to be dependent on whether the value was recorded during a single phase of loading [7][8][9]14,23,24] in which case the reported value will include large irrecoverable plastic strains, or whether values were recorded during the unloading phase of repeated load cycles [22,25] or following repeated impactions [2]. Phillips et al [25] found that the elastic behaviour of MCB was strongly dependent on the stress environment it was subjected to.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…While some variations are expected due to inter-sample variations, such a large range has to be due to other factors. The reported values are seen to be dependent on whether the value was recorded during a single phase of loading [7][8][9]14,23,24] in which case the reported value will include large irrecoverable plastic strains, or whether values were recorded during the unloading phase of repeated load cycles [22,25] or following repeated impactions [2]. Phillips et al [25] found that the elastic behaviour of MCB was strongly dependent on the stress environment it was subjected to.…”
Section: Introductionmentioning
confidence: 92%
“…In this study a relationship between the elastic modulus, E and the applied pressure, p is developed. It has also been found that MCB exhibits visco-elastic material properties [19,22,25], and this study presents a quantitative description of the time-dependent elastic properties of MCB.…”
Section: Introductionmentioning
confidence: 97%
“…Bioactive ceramics such as hydroxyapatite, betatricalcium phosphate, and calcium metaphosphate (CMP) are known to provoke specific biological responses at the interface of the materials resulting in the formation of a strong bond between the tissue and materials [12]. Also, it has been proved that the bioceramics enhance osteoblast differentiation as well as osteoblast growth (osteoconductive property) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ohashi et al (1999) increased the confined compressive modulus of their impaction specimens by over an order of magnitude (from 0.20 to 3.71 MPa) by using a morselization technique that resulted in an MCB size distribution with more larger pieces, along with compacting the specimens 30 times rather than 15 times. Two studies that both used finely milled corticocancellous bone (although the mill designs were different) reported vastly different confined compression moduli: Ohashi et al (1999) reported a modulus of 0.20 MPa with specimens compacted 15 times (to 53 MPa) and then compressed quasistatically, while Verdonschot et al (2001) reported a modulus of 85 MPa with specimens compacted manually and then compressed dynamically 98 times (to 2.68 MPa). Two groups that tested MCB under triaxial compression (with similar transverse confinement pressures) reported modulus values that differed by an order of magnitude-9.44 MPa (Rennirt et al, 1997) vs. 100 MPa (Brodt et al, 1998).…”
Section: Discussionmentioning
confidence: 97%